2009
DOI: 10.1002/app.31524
|View full text |Cite
|
Sign up to set email alerts
|

Performance of fibers embedded in a cementitious matrix

Abstract: Reinforcement of cementitious materials with short fibers has been proved to be an economical and effective way to convert these brittle materials to ductile products. Many fibers with different geometries have been used as reinforcement materials. Fibers bonding to cementitious materials play an important role in mechanical performance of these composites. This article describes the performance of (homemade) fibers as reinforcement in cement-based materials by investigation on bonding characteristic of fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…23,24 Both triangular and trilobal fibers have a shape factor (S.F.) more than 1 which is in favor of attaining high mechanical interlocking with the surrounding matrix.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 Both triangular and trilobal fibers have a shape factor (S.F.) more than 1 which is in favor of attaining high mechanical interlocking with the surrounding matrix.…”
Section: Methodsmentioning
confidence: 99%
“…The wet spun Acrylic fiber has shown better performance in bonding to the cementitious materials in comparison to the dry spun fiber [10,21]. To assess the accurate dimensions of the non-round fibers, the image processing software that allows segmenting the cross section of the fibers was employed.…”
Section: Fibers Propertiesmentioning
confidence: 99%
“…The high and very low fiber/matrix interface strength leads to a tendency of fiber rupture and easy fiber pull-out, respectively, which limits the tensile strain capacity and energy absorption of the resulting composite. It has been found that low modulus polymeric fibers generally result in strain softening behavior due to their low tensile capacity [10,[20][21]29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Although PP and PE fibers have hydrophobic characteristics and poor bonding with the cement matrix, these fibers are considered to be attractive for the reinforcement of cement matrices due to their high resistance to the alkaline environment of the cement matrix ($12.5 pH) and their low cost. 6,12 Pakravan et al 7 examined the performance of different fibers such as glass, polypropylene, polyacrylonitrile (PAN) and high-strength nylon 66, used as reinforcement for cement-based composites. It was reported that the reinforcing efficiency strongly depended on interfacial contact area in fiber/matrix interface and chemical and physical properties of fibers.…”
Section: Introductionmentioning
confidence: 99%